Impact of Online Reviews on Gen Z's Halal Food Purchase Decisions in Tasikmalaya - Andani, Listia; Bundo, Mayang; Faiz Izzuddin, Ahmad (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
This study aims to develop a conceptual framework to explore how review timeliness, review quantity, and review valence impact online purchasing decisions for halal food among Gen Z consumers. Utilizing purposive sampling, the study surveyed 400 Gen Z Muslims and applied structural equation modeling-partial least squares (SEM-PLS) for analysis. The results reveal that review timeliness, review quantity, and review valence significantly and positively influence online purchasing decisions for halal food within this demographic. Notably, this research offers a novel contribution by focusing specifically on the effects of these online review factors on Gen Z's halal food purchasing behaviors, a context often overlooked in broader studies. The findings are limited to respondents from Tasikmalaya, suggesting that future research could expand to include samples from various regions or countries to improve generalizability. Companies are encouraged to enhance the positive perception of their products to better engage this market segment.